If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -7 + -1z + 3 = 0 Reorder the terms: -7 + 3 + 3z + -1z = 0 Combine like terms: -7 + 3 = -4 -4 + 3z + -1z = 0 Combine like terms: 3z + -1z = 2z -4 + 2z = 0 Solving -4 + 2z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2z = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 2z = 0 + 4 2z = 0 + 4 Combine like terms: 0 + 4 = 4 2z = 4 Divide each side by '2'. z = 2 Simplifying z = 2
| y+2x=-6 | | 3y-2x=-2 | | 3(b+1)=4b+1 | | x-y-5=0 | | 10a^3+7a^2+1a= | | 8x+12=10x-18 | | (3m+8n)(3m-8n)= | | 12=3b+6a | | 5(10y-2)=2(2y+20) | | a+15=18 | | 50x+278=850 | | 16x-43=-33 | | 0=x^2+8x-16 | | -3=-3(1-4a) | | 7x-9=3x+31 | | 3.21-7y=10y-1.84 | | 29x^2-29x=0 | | t-1.3=-5.3 | | 7x+8=5x+10 | | (1-9a)(1-7a)= | | 3x-4+2x=21 | | (1-4a)(1-9a)= | | -3(X+4)=-8X | | 2y-2x=14 | | x^2+2x-63= | | -6(-6k+7)-8k=70 | | x*x-x=.3125 | | a+25=18 | | 4m-5=15 | | 3(6)-5=y | | -3(x+3)-5(1+7x)=62 | | 3c+12=-7 |